Mikropropagasi Tanaman Manggis (Garcinia mangostana) - Ika Roostika; Novianti Sunarlim; Ika Mariska (Jurnal AgroBiogen, 2005)
The conventional propagation of mangosteen plant is still facing some problems, such as the limited fruiting season and number of seedling, and slow growth of seedling. In vitro culture is an alternative technique to solve the problems. An experiment was done to obtain a suitable micropropagation technique for mangosteen plant through in vitro culture with high level of shoot multiplication and root formation, as well as high level of acclimated shoot or planlet growth. The treatments for shoot induction and axillary bud multiplication of mangosteen were three levels of BA (1, 3, and 5 mg/l) on the MS basal medium. The treatments for root induction were combinations between two kinds of basal medium (MS and WPM), two formulations of the media (full strength and 1/4 strength), and two levels of IBA (5 and 10 mg/l). Root induction was also done ex situ by dipping the shoots in IBA solutions (100-200 ppm) for 1-2 hours, followed planting onto the best acclimation media. The acclimation was done using two different media (soil only and soil + compost) under two different environments (green house and incubation room + green house). Results of the experiment showed that the highest percentages of seed growth and number of shoots per seed was obtained on the basal medium containing 5 mg/l BA. The highest number of axillary bud multiplication was obtained on the medium with 3 mg/l BA. MS medium + 5 mg/l IBA promoted 75% rooting. The plant acclimatization on soil + compost in the green house with 75% shading promoted the fastest plant growth. During the acclimatization, up to 75% of the shoots treated with dipping in 100 ppm IBA solution for one hour grew well. After four months, the roots of the plant developed secondary and tertiary roots.